Research progress in small fiber neuropathy associated with Sjogren's syndrome - Liying XU; Jiayu ZHANG; Erpeng WANG; Yuxin LIU; Chao YUAN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Small fiber neuropathy (SFN) in peripheral neuropathies is the most common neuropathy associated with Sjogren's syndrome (SS). Small fiber neuropathy is a neuropathy that specifically involves myelinated Aδ and unmyelinated c-fibers, with abnormal neurophysiology and/or reduced intraepidermal nerve fiber density in the skin biopsy. Patients with Sjogren's syndrome complicated with small fiber neuropathy often present with painful and burning sensation, accompanied by autonomic dysfunction. In these patients, neurologic clinical manifestations may precede the diagnosis of Sjogren's syndrome. Thus, early diagnosis and treatment may help to reduce the suffering of the patients. This article reviews the research progress in small fiber neuropathy associated with Sjogren's syndrome, including the pathological basis, possible molecular mechanisms, clinical symptoms, the diagnosis and treatment in order to benefit the research, diagnosis and management of this disease.